Primary hip replacement prostheses and their evidence base: systematic review of literature. Issue 15 (9th July 2014) - Kynaston-Pearson, F; Ashmore, A M; Malak, T T; Rombach, I; Taylor, A; Beard, D; Arden, N K; Price, A; Prieto-Alhambra, D; Judge, A; Carr, A J; Glyn-Jones, S
Abstract : STUDY QUESTION: To what extent are prostheses with no readily available evidence to support their use being implanted in primary total hip arthroplasty? SUMMARY ANSWER: A quarter of prostheses available to orthopaedic surgeons in England and Wales have no readily available evidence of clinical effectiveness to support their use. WHAT IS KNOWN AND WHAT THIS PAPER ADDS: The high failure rate of some metal-on-metal hip replacements has highlighted the need for an adequate evidence base for orthopaedic implants. A considerable number of prostheses available to the surgeon for use in primary total hip arthroplasty in the UK have no available evidence of clinical effectiveness to support their use.